Clinical Efficacy and Mechanism of Vitamin D2 in Treating Hashimoto’s Thyroiditis - Gan L; Li Y (Dove Medical Press, 2024)
Lu Gan, Yuqi Li Department of Endocrinology, General Hospital of Ningxia Medical University, Yinchuan City, 750000, People's Republic of ChinaCorrespondence: Lu Gan, Ningxia Medical University General Hospital, 804 Shengli Street South Street, Yinchuan City, 750000, People's Republic of China, Tel +86-13709518674, Email 13709518674@163.comObjective: Hashimoto's thyroiditis (HT) is one of the most common autoimmune diseases, with the highest incidence rate among autoimmune thyroid disorders. Vitamin D2 may have therapeutic effects on HT. This study aimed to elucidate the molecular mechanisms underlying vitamin D2 therapy for HT.Methods: Differentially expressed genes (DEGs) associated with vitamin D2-treated HT were identified, and the DEG-associated gene enrichment pathway was explored using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses. The correlation between the hub genes and infiltrating immune cells was investigated, and the interactions among the hub genes and target drug and competing endogenous RNA (ceRNA; long non-coding RNA [lncRNA]-microRNA [miRNA]-messenger RNA [mRNA]) regulatory networks were determined.Results: GO and KEGG enrichment analyses identified a total of 102 DEGs (6 upregulated and 96 downregulated) in the vitamin D2-treated group samples. The area under the curve values of the identified 10 hub genes was as follows: CCR1(0.920), CXCL1 (0.960), CXCL8 (0.960), EGR1 (0.960), FCGR3B (0.920), FOS (1.000), FPR1 (0.840), MMP9 (0.720), PTGS2 (0.960), and TREM1 (1.000). The immune enrichment scores of the mast cell (P = 0.008), neutrophil (P = 0.016), and plasmacytoid dendritic cell (P = 0.016) were significantly decreased in the vitamin D2-treated group (P < 0.05). The hub gene/drug regulatory network included 8 hub genes, 108 molecular drugs, and 114 interaction relationship pairs. The ceRNA regulatory network included 129 lncRNAs, 145 miRNAs, mRNAs (hub genes), and 324 interaction relationship pairs.Conclusion: Vitamin D2 may play an immunomodulatory role by regulating the aforementioned immune-related molecules and immune cells, thereby improving its therapeutic effects on HT.Keywords: Hashimoto's thyroiditis, vitamin D2, RNA sequencing, differentially expressed genes, immune infiltration